2017
DOI: 10.1097/ijg.0000000000000715
|View full text |Cite
|
Sign up to set email alerts
|

Micropulse Cyclophotocoagulation: Initial Results in Refractory Glaucoma

Abstract: MP-TSCPC is effective at lowering IOP and decreasing the need for ocular antihypertensive medications. Eyes with limited visual potential or at high risk for incisional glaucoma surgery can successfully be treated with MP-TSCPC as a reasonable and effective alternative to traditional CPC. These results present short-term data and both longer follow-up and further studies are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
81
4
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(101 citation statements)
references
References 11 publications
5
81
4
2
Order By: Relevance
“…Micropulse CPC (MP-CPC) seems more efficient than UC3 in refractory glaucoma, inducing more than 40% reduction in IOP at 12 months after surgery but reduced efficacy with time. [27] DL-CPC allows for a 44% mean reduction in IOP at 19 months in eyes with higher baseline IOP (36 mmHg). [28] In all previous major studies, the procedure was reported as safe without serious intra-or postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…Micropulse CPC (MP-CPC) seems more efficient than UC3 in refractory glaucoma, inducing more than 40% reduction in IOP at 12 months after surgery but reduced efficacy with time. [27] DL-CPC allows for a 44% mean reduction in IOP at 19 months in eyes with higher baseline IOP (36 mmHg). [28] In all previous major studies, the procedure was reported as safe without serious intra-or postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Although it has been suggested to have a safer profile in comparison with traditional transcleral cyclophotocoagulation (TCP), the following complications have been described with MP-TCP: hypotony, intraocular pressure (IOP) spike, prolonged anterior chamber inflammation, macular edema, corneal edema, phtisis bulbi, and transient hyphema in cases with neovascular glaucoma. 1 , 2 , 3 , 4 , 5 , 6 The aim of this case report is to present two cases of severe neurotrophic keratopathy (NK) after MP-TCP. To our knowledge, these post-MP-TCP complications have not been previously described in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The authors indicate that eye size is the most useful factor in determining the duration of an illness. Chronic glaucoma is the only reason for the increase in the eyeball in size and the development of buphthalmia [8,9,10,11]. In almost all cases, the enlarged eye is irreparably blind.…”
Section: Introductionmentioning
confidence: 99%
“…A thorough ophthalmic examination should help to determine if the case is primary or secondary. If the patient has a lens dislocation, this will affect on the prognosis and choice of treatment, lens extraction will be necessary for successful state management [8,9]. The diagnosis of lens dislocation is based on the study of the anterior segment, for its visualization using a slit lamp, in addition, visualization of the lens using ultrasound examination of the eye is possible [8,10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation